The ‘evil arrow’ myths and misconceptions of cancer at Lagos University Teaching Hospital, Nigeria - Ololade, Kehinde; Alabi, Adewumi; Fadipe, Babatunde; Adegboyega, Bolanle (South Afri‪can journal of oncology, 2019)
Background: Myths and misconceptions have significant impact on the presentation and management of cancers globally. One such example includes ‘evil arrow’ myths. There is limited knowledge regarding the role of misconceptions in late presentation for management in developing countries. The percentage increase in cancers in many African countries is higher than that in developed countries. Evil arrow is the seeming attack of the enemy in a supernatural version as a result of wizardry. Aim: To evaluate the relationship of common myths and misconceptions among cancer patients, their treatment and delay of presentation to the hospital. Setting: The study was undertaken in a tertiary health facility in a cosmopolitan tropical state. Method: This is a randomised observational survey study carried out among patients and their relatives referred to the Radiotherapy Clinic of the Lagos University Teaching Hospital for treatment (a lower-income mixed metropolitan setting). A self-administered questionnaire was used. Patient consent was obtained. Data were analysed with Epi Info 2002 software and the results were presented using frequency tables and charts. Results: About 57 were patients (67%) and 28 were patients’ relatives (33%). The age distribution of participants showed 31–40 years (31.8%; 27) as the highest number, while 11–20 years (1.2%; 1) was the lowest number. A slight female preponderance of 58.8% (50) was observed. High incidence of those with the opinion that cause of cancer is unknown represented 63% (54). Over 65% of patients presented with advanced disease. The reasons for late presentation to the hospital included lack of funds in 23.5% of patients (20). Conclusion: Lack of funds, myths and misconception are main reasons why patients presented late to hospital. There is a need to emphasise debunking innumerable myths and misconceptions associated with cancer.
openalex: W2913767481 mag: 2913767481
Keywords: openalex:import

Side effects of radiotherapy on breast cancer patients in the Department of Radiotherapy, Lagos University Teaching Hospital, Idi-Araba, Lagos, Nigeria - Sowunmi, Anthonia; Onuoha, Peace C; Alabi, Adewumi; Okoro, Uchenna Samuel (Journal of clinical sciences, 2020)
Background: Side effects of radiotherapy (RT) could be temporary or permanent, can be severe, and affect quality of life. An investigation into the side effects of RT on breast cancer patients would help evaluate the incidences and associated risk factors in the low-income countries for patients undergoing RT in order to ensure maximum treatment with very minimal side effects. Objective: To assess the side effects of RT in patients with breast cancer undergoing RT in Lagos University Teaching Hospital. Materials and Methods: This was a descriptive, cross-sectional study. Self-administered questionnaires were distributed to breast cancer patients on RT that have received treatment for at least 2 weeks at the RT Department between March and August 2016. A total of 146 questionnaires were distributed, whereas 139 were completely filled and returned for the evaluation and analysis, given a response rate of 95.2%. Results: The common side effects noticed from the analysis of this research work included skin erythema (87.1%), fatigue (74.1%), telangiectasia (69.1%), pain (89.9%), breast swelling (45.3%), and loss of hair in the armpit and chest area (87.1%), and the less common ones were breast shrinkage (20.1%), lymphedema (41.0%), cardiac complications (30.9%), lung problems (12.9%), sore throat (7.9%), brachial plexopathy (24.5%), and damage to the bones (ribs; 3.6%). Management of the side effects by patients revealed that 30 (21.6%) used analgesics, 28 (20.1%) used steroidal cream, 27 (19.4%) avoided deodorants and antiperspirant, 22 (15.8%) exercised, 15 (10.8%) took antibiotics, 10 (7.2%) took herbs, and 7 (5%) had to stop treatment temporarily for minimum of a week due to severe morbidity. Conclusion: A large percentage of breast cancer patients undergoing RT experience painful side effects (89.9%), of these 87% experience skin erythema, 74% experience fatigue, and 69% experience telangiectasia.
openalex: W3024891548 mag: 3024891548
Keywords: openalex:import

Review of radiation oncology emergencies in Lagos University Teaching Hospital, Nigeria - Adegboyega, Bolanle; Sowunmi, Anthonia; Alabi, Adewumi; Ojifinni, Oludoyinmola Omobolade; Adenipekun, A (South African journal of oncology, 2019)
Background: Radiation oncology emergencies (ROEs) are common in metastatic or locally advanced cancer accounting for a large proportion of radiotherapy indications in poor resource settings. Aim: To review pattern, presentation and outcome of ROEs in Lagos University Teaching Hospital (LUTH) and compare with an earlier study in the northern part of the country for possible geographical variation. Setting: A retrospective review of ROE record from 2008 to 2016 in LUTH. Method: Demographic data, clinical presentation, treatment and outcomes were analysed using charts and frequency tables. Results: Total of 458 cases of oncologic emergencies were reviewed. The mean age was 52.3 years with a male-to-female ratio of 1:2.2. The majority (85%) of the patients presented in stage IV, 10% stage III and 5% stage II diseases. Spinal cord compression was the commonest presentation seen in 53.9% of cases, brain metastases in 22.1% of patients and tumour haemorrhage in 22.5% of patients. Time from the onset of symptoms to treatment was between 24 and 48 h in 16.4%, > 48 h to 1 week in 64.4% and above 1 week in 19.2%. There was a complete or significant response in signs and symptoms in 77%, no improvement in 11% and 1.1% had disease progression. Conclusion: This study showed a varied pattern of presentation in ROEs from what was obtained in northern Nigeria, with spinal cord compression being the commonest in south west Nigeria. Despite a delayed onset in treatment, radiation therapy is vital in oncology emergencies management. There is a need for accessible functional radiotherapy centres in Nigeria to combat the delays in commencing treatment.
openalex: W2961553842 mag: 2961553842
Keywords: openalex:import

Visual impairment and ocular morbidities among schoolchildren in Southwest, Nigeria - Alabi, Adegboyega Sunday; Aribaba, Olufisayo Temitayo; Alabi, Adewumi; Ilo, Olubanke Theodora; Onakoya, Adeola O; Akinsola, F B (Nigerian Postgraduate Medical Journal, 2018)
The purpose of this study was to determine the prevalence of visual impairment and ocular morbidities among primary and secondary schoolchildren aged 5 years to <l6 years in Ifo, Ifo Local Government Area in Ogun State, Nigeria.The study was a population-based descriptive cross-sectional study conducted among schoolchildren aged 5 years to <16 years old attending primary and secondary schools in Ifo, Ifo Local Government Area of Ogun State. Multistage sampling technique was used for the study. After enumeration and questionnaire administration, the visual acuities of all respondents were measured, followed by examination of the anterior and posterior segment structures of the eyes of the children.A total of 1308 schoolchildren (574 males and 734 females) participated in the study with a mean age of 12.03 years (standard deviation = ±2.572 years). Eighty-seven (6.7%) children had visual impairment and 224 (17.1%) children had ocular morbidities. Of the 87 children with visual impairment, 61 (70.1%) had mild impairment, 19 (21.8%) had moderate impairment and 7 (8.0%) had severe impairment. The common ocular morbidities identified were refractive error 39.7%, high/asymmetrical vertical cup-to-disc ratio (suggestive of glaucomatous optic neuropathy) 33.5%, allergic conjunctivitis 19.2%, corneal opacity 2.7% and lenticular opacity 2.2%. Ocular morbidities identified among children with severe visual impairment were refractive error 5 (71.4%), allergic conjunctivitis and corneal opacity 1 (14.3%) each.The study concluded that with the prevalence of 6.7% of visual impairment and 17.1% of ocular morbidity, it will be beneficial to establish a sustainable school eye health services in schools in Ifo.
openalex: W2894035650 mag: 2894035650
Keywords: openalex:import

Training Teachers on Vision Screening for School Children in Low-Resource Setting in Southwest, Nigeria - Aribaba, Olufisayo Temitayo; Alabi, Adegboyega Sunday; Alabi, Adewumi; Adenekan, Adetunji Olusesan; Onakoya, Adeola O; Akinsola, F B (Nigerian journal of ophthalmology, 2019)
Background: There is a growing recognition that school teachers can be trained to deliver simple health and screening services and refer children for treatment if they have health problems. Although it is recognized that teachers are not replacement for qualified health personnel, they can be trained to provide simple vision screening for school children. Aim: This article aims to determine the ability of trained school teachers to participate in the school eye screening program by testing visual acuity (VA) of the primary and secondary school children aged 5 to 15 years using the Snellen’s chart in Ifo, Ifo Local Government Area of Ogun State. Materials and Methods: This study was a population-based descriptive cross-sectional study conducted among school children aged 5 to 15 years from 20 primary and secondary schools in Ifo, Ifo Local Government Area of Ogun State. Forty teachers (two per school) were trained to use the Snellen’s chart to measure VA and categorize vision into normal or impaired using the VA of 6/9 in the better eye as cutoff. After enumeration, the visual acuities of the school children were measured using the Snellen’s chart by the teachers and compared with visual acuities measured by the research team. Results: A total of 1308 school children (574 boys and 734 girls) had their VA tested using Snellen’s chart by 40 teachers and verified by the research team. The sensitivity of the teachers’ VA testing was 73.6%, with a high specificity of 93.8% and positive and negative predictive values of 45.7% and 98%, respectively. The teachers’ VA measurements showed a moderate agreement with that of the researchers with a Kappa score of 0.525. Conclusion: This study shows that school teachers can be trained to participate in school eye health program. Their involvement can make the program cheaper to establish, ensuring sustainable and better coverage among the targeted student population.
openalex: W2953675919 mag: 2953675919
Keywords: openalex:import

Patient's perception on the quality of radiotherapy services in two teaching hospitals in Nigeria - Sowunmi, Anthonia; Fatiregun, Omolara; Alabi, Adewumi; Zaccheus, Ibitoye A; Kingsley, Irurhe A; Oyedeji, Shola (Nigerian journal of medicine : journal of the National Association of Resident Doctors of Nigeria, 2015)
OBJECTIVE: Patient satisfaction is an important and commonly used indicator for measuring the quality in health care. Patient satisfaction affects clinical outcomes, patient retention, and medical malpractice claims. It affects the 13 timely, efficient, and patient-centered delivery of quality health care13.A review of quality of services from the patient's perspective could be a method of assessing in order to improve servicesand achieve total quality management. This study was designed to assess patients' perception on the quality of Radiotherapy services in Lagos University Teaching Hospital (LUTH) Lagos and University College Hospital (UCH) Ibadan. METHODOLOGY: This study is a cross-sectional study. This research lasted for a period of two months and all patients receiving radiotherapy within is period were included in this study. A total of 246 questionnaires were completed (152 and 94 in LUTH and UCH respectively) and the data collection was by semi-structured questionnaire. Data obtained were collected and analyzed using SPSS statistics [Social Sciences Statistical Package] 17.0 version. RESULTS: The findings of this research indicated that 68.4% in LUTH and 53.2% in UCH of the patients experienced good care. It also revealed that there is good interaction between the staff and the patient. Most of the patients spent more than 3 hours before receiving treatment and also the reason for such delay were not explained to them. The rate of preferential treatment was noted to be high. CONCLUSION: This study will contribute positively towards achieving effective and qualitative radiotherapy services by creating awareness for the need to minimize patient waiting time as well as the need to explain the reason for such delays. The department should adopt better ways of appointment system so that treatment will be on first come first serve basis. This study will contribute positively towards achieving effective and qualitative radiotherapy services by creating awareness for the need to minimize patient waiting time as well as the need to explain the reason for such delays. The department should adopt better ways of appointment system so that treatment will be on first come first serve basis.
openalex: W2526423058 mag: 2526423058
Keywords: openalex:import

Evaluation of Three-Dimensional Conformal Radiotherapy and Intensity Modulated Radiotherapy Techniques for Left Breast Post-Mastectomy Patients: Our Experience in Nigerian Sovereign Investment Authority-Lagos University Teaching Hospital Cancer Center, South-West Nigeria - Adeneye, Samuel Olaolu; Akpochafor, Michael Onoriode; Adegboyega, Bolanle; Alabi, Adewumi; Adedewe, Nusirat; Joseph, Adedayo; Fatiregun, Omolara; Omojola, Akintayo Daniel; Adebayo, Abe; Oluwadara, Esther (The Journal of Breast Health, 2021)
This study aimed to evaluate the dosimetric properties of treatment plans obtained from three-dimensional conformal radiotherapy (3D-CRT) and intensity-modulated radiotherapy techniques (IMRT) plans for left chest wall breast cancer patients.A total of 20 patients with left-sided chest wall radiotherapy were randomly selected with the dose prescriptions: 42 Gy and 45 Gy in 15 and 18 fractions, respectively. Treatment plans were obtained using 3D-CRT and IMRT for each patient. Five to seven beams were used for IMRT, while tangential beams were used for 3D-CRT. Planning target volume, Dnear-max (D2 ), Dnear-min (D98 ), Dmean, Homogeneity and Conformity Indices (HI and CI) were obtained. Similarly, mean doses to organs at risk (OAR), V5, V10, V20, V25 were generated from the dose-volume histogram and compared.IMRT showed a significant improvement in HI compared to 3D-CRT (p<0.0001). Although there was no significant difference in sparing of the left lung between both plans for high-dose volumes (V20: 18.2 vs 30.55, p<0.0001), (V25: 11.17 vs 28.12, p<0.0001). IMRT however showed supremacy to 3D-CRT with high-dose volumes for the heart, including V20 (4.44 vs 10.29, p = 0.02), V25 (2.08 vs 8.94, p = 0.002). 3D-CRT was better than IMRT in low-dose volumes for left lung (V5: 92.23 vs 56.60, p<0.001; V10: 60.98 vs 47.20, p = 0.04) and heart (V5: 57.45 vs 30.39, p = 0.004).IMRT showed better homogeneity and sparing of high-dose volumes to OAR than 3D-CRT. On the other hand, 3D-CRT showed a reduction of low-dose volumes to OARs than IMRT.
openalex: W3176914785 mag: 3176914785
Keywords: openalex:import